IMPACT OF PARENTS’ SOCIAL ECONOMIC STATUS ON STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN KIENI EAST SUBCOUNTY, NYERI COUNTY, KENYA - Mwariri, Monicah Wahito; Marete, Jacob Bundi; Mwenda, Eric Gitonga (IJRDO- Journal of Educational Research, 2017)
There are several impediments to students’ academic performance, among them the parents’social economic status (SES), which is thought to influence students’ academic achievement.The purpose of this study was to find out the impact of social economic status on students’academic performance in public secondary schools in Kieni East Sub County, Nyeri County,Kenya. The study established that the number of family members in formal employment,coupled with employment and business/self-employment income, led to higher academicperformance among students. The findings also revealed that in homes lacking academic supportfacilities; the academic performance of learners was poor, while homes with adequate facilitiesboosted the academic performance of the students.